2017
DOI: 10.2217/nnm-2017-0237
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of core-shell Intrinsic Defect Induced Enhanced Antibacterial Activity of ZnO Nanocrystals

Abstract: Synthesized nano ZnO exhibit size-dependent antibacterial action as consequences of interactions with cell membrane proteins via hydrogen bond interaction with amino acid residues followed by internalization, membrane depolarization and induction of reactive oxygen species generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 105 publications
3
33
0
1
Order By: Relevance
“…Synthesis of metallic oxide nanoparticles such as ZnO has been reported by HEBM in previous studies. 47 Similar changes in physiochemical properties of ZnO nanoparticles have been reported in the case of zinc oxide in the previous literature reported by our group and other groups. 47 50 These results have revealed the change in physiochemical properties of TiO 2 nanoparticles with milling time and speculated their change in the biological effect accordingly.…”
Section: Discussionsupporting
confidence: 89%
“…Synthesis of metallic oxide nanoparticles such as ZnO has been reported by HEBM in previous studies. 47 Similar changes in physiochemical properties of ZnO nanoparticles have been reported in the case of zinc oxide in the previous literature reported by our group and other groups. 47 50 These results have revealed the change in physiochemical properties of TiO 2 nanoparticles with milling time and speculated their change in the biological effect accordingly.…”
Section: Discussionsupporting
confidence: 89%
“…Size, shape, and morphology of the metal nanoparticles are strongly influenced by the metabolites in the plant extract, which leads to the formation of nanoparticles of high stability with narrow size distribution [ 86 , 87 ]. Plant metabolites are terpenoids, polyphenols, sugars, alkaloids, phenolic acid, and proteins which play an important role in the binding and reduction of metal ions, thus thereby yielding metal nanoparticles as shown in Fig.…”
Section: Various Techniques For Nanoparticle Synthesismentioning
confidence: 99%
“…Some works have evidenced ZnO nanoparticles with dimensions smaller than 100 nm have shown increasing antimicrobial properties against Gram-negative and Gram-positive bacteria due to a higher cellular internalization. Specifically, Verma et al (2018) studies have indicated that the antibacterial activity of ZnO nanoparticles against Staphylococcus aureus and Escherichia coli increased with the decrease in their size from 250 to 80, 40, and 20 nm due to an increased reactive oxygen species generation and membrane damage in bacteria [11,12]. Different synthesis methods as sol-gel, hydrothermal, simple thermal sublimation, vapor-liquid-solid, double-jet precipitation, self-combustion, and "green synthesis" have been used to obtain ZnO nanorods, nanospheres, nanotubes, nanowires, and nanoneedles [13][14][15].…”
mentioning
confidence: 99%